Faktor Faktor Yang Berhubungan Stunting Pada Balita Usia 24 S/D 59 Bulan Di Desa Kalukutinggu Kecamatan Dolo Barat Kabupaten Sigi: Factors Associated with Stunting in Toddlers Aged 24 to 59 Months in Kalukutinggu Village, Dolo Barat District, Sigi Regency - Iriani, Indri (Jurnal Kolaboratif Sains, 2025)
Introduction: Stunting is a global health problem that can hinder a nation's future. Indonesia holds the second-highest rate of stunting in Southeast Asia. This issue is caused by various factors, ranging from the nutritional status of pregnant mothers, parenting patterns, sanitation, to the family's socioeconomic conditions. This study aims to analyze the factors associated with stunting in toddlers aged 24 to 59 months in Kalukutinggu Village, Sigi Regency. Methods: This study used a qualitative design with a descriptive-analytic approach. Sampling was conducted using a purposive sampling technique with a total of 30 respondents. Data were collected through questionnaires, structured interviews, observation, and anthropometric measurements. Data analysis was performed univariately to describe each variable and bivariately using the Chi-Square (X2) statistical test to examine the relationships between variables. Results: The study results show that most respondents married at a young age (46.7% at ages 5–18) , had a low level of education (86.7%) , and low income (86.7%). Nevertheless, univariate analysis indicated that the majority of respondents (80%) had a good nutritional status during pregnancy, adequate parenting patterns, good sanitation, and access to clean water. Of the 30 toddlers studied, 5 (16.7%) were stunted. The bivariate analysis showed no statistically significant relationship between the combination of risk factors (maternal nutritional status, parenting patterns, sanitation, education, and income) and the incidence of stunting (p-value = 0.593 > 0.05). Conclusion: This finding is likely due to the small sample size, the combination of variables, or other unmeasured causal factors, such as a history of recurrent infectious diseases. Nonetheless, demographic issues such as early-age marriage, low education, and low income remain key concerns with the potential to be the root causes of stunting. Stunting was found in Kalukutinggu Village, even though the measured risk factors did not show a statistically significant relationship.